Uniting or Dividing? Digital Sermons and Sectarian Debates among Muslim Preachers on Facebook in Bangladesh - Md. Mahdi Hasan; Bhirawa Anoraga (Digital Muslim Review, 2024)
This paper examines how Facebook is transforming religious authority and amplifying sectarian discussions through digital sermons (waʿẓ) delivered by three prominent preach-ers in Bangladesh: Shaykh Dr. Muzaffar b. Mohsin, Muftī Rezaul Karim Abrar, and Muftī Gias Uddin Tahery. Using a netnographic approach, we analyse the discourses promoted in their sermon videos on Facebook. We demonstrate how Facebook incentivises religious leaders to intensify sectarianism in order to increase online engagement and reinforce their authority. Thus, although the Internet—specifically Facebook—is often assumed to have the potential to connect the Muslim umma, it simultaneously exacerbates sectarian divi-sions, with significant implications for both religious and social dynamics in Bangladesh.